Preoperative administration of cephalosporins for elective caesarean delivery - Bogavac Mirjana (Srpski Arhiv za Celokupno Lekarstvo, 2010)
Introduction. Antibiotic prophylaxis means administration of antibiotics in prevention of infections. Objective. To investigate the efficacy of a single dose preoperative administration of ceftriaxone and cefazolin in the prevention of intra- and postoperative infections in the parturients without high risk of inflammation. Methods. The first group of 45 pregnant and 4 non-pregnant women were preoperatively administered ceftriaxone in a dose of 2 g, i.v., 10 minutes before the planned surgery. The second group of 45 pregnant and 4 non-pregnant women were preoperatively administered cefazolin in a dose of 2 g i.v., 10 minutes before the planned surgery. The concentrations of antibiotics were estimated immediately and 6 hours following the operation, as well as in the amniotic fluid and umbilical cord in the group of pregnant women. The estimation of antibiotic concentration was done by the method of liquid chromatography. Results. The mean concentrations of antibiotics in the patients following the elective caesarean section were as follows: ceftriaxone - 22.7 μg/l. vs cefazolin - 44.8 μg/l. Six hours later, the concentration of antibiotic decreased, but the concentration of cefazolin was still over the MIC for sensitive bacteria. The mean concentrations of antibiotics following gynaecological surgery in the non-pregnant patients were as follows: ceftriaxone - 12.0 μg/l vs cefazolin - 30.1 μg/l. Six hours later, the concentration of antibiotic decreased. Conclusion. It is most optimal to administer a single-dose of the first generation cephalosporins-cefazolin-immediately following the clamping of the umbilical cord as well as in preoperative prophylaxis in gynaecological operations.